2019
DOI: 10.1111/jfpp.13881
|View full text |Cite
|
Sign up to set email alerts
|

Storage temperature without fluctuation enhances shelf‐life and improves postharvest quality of peach

Abstract: Peaches (Prunus persica) were packaged in two kinds of gas environments: the steady‐state controlled atmosphere (CA) of 10% O2 and the modified atmosphere (MA) of polyethylene bag. Based on 1ºC, storage temperature was set four fluctuation values: 1 ± 0ºC, 1 ± 0.5ºC, 1 ± 1ºC and 1 ± 2ºC. Results indicate that postharvest quality of peach under temperature without any fluctuation (1 ± 0ºC) was effectively maintained by reducing respiration rate and polyphenol oxidase activity. The total soluble solid content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Pelletier, Brecht, Cecilia do Nascimento Nunes, and Émond (2011) reported that strawberries were found to have deteriorated in terms of moisture content and poor visual quality while being transported to the retailer, especially when TF varied from 0.7 to 3.7°C during the precooling, cold storage, transport, and retail stages. Pan et al (2019) compared the storage quality of peach in the 1 ± 0°C, 1 ± 0.5°C, 1 ± 1°C, and 1 ± 2°C conditions, and found that TF was not conducive to peach preservation. The evidence for this was higher respiration rate and polyphenol oxidase (PPO) activity, and poorer firmness, soluble solids content, and superoxide dismutase (SOD) activity compared to constant storage temperature.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelletier, Brecht, Cecilia do Nascimento Nunes, and Émond (2011) reported that strawberries were found to have deteriorated in terms of moisture content and poor visual quality while being transported to the retailer, especially when TF varied from 0.7 to 3.7°C during the precooling, cold storage, transport, and retail stages. Pan et al (2019) compared the storage quality of peach in the 1 ± 0°C, 1 ± 0.5°C, 1 ± 1°C, and 1 ± 2°C conditions, and found that TF was not conducive to peach preservation. The evidence for this was higher respiration rate and polyphenol oxidase (PPO) activity, and poorer firmness, soluble solids content, and superoxide dismutase (SOD) activity compared to constant storage temperature.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Pan et al. (2019) compared the storage quality of peach in the 1 ± 0°C, 1 ± 0.5°C, 1 ± 1°C, and 1 ± 2°C conditions, and found that TF was not conducive to peach preservation. The evidence for this was higher respiration rate and polyphenol oxidase (PPO) activity, and poorer firmness, soluble solids content, and superoxide dismutase (SOD) activity compared to constant storage temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Although the respiratory rate increased slightly in the course of 9–15 days, it showed a downward trend during storage. Previous studies have shown that temperature fluctuations can cause changes in the respiratory intensity and gas transmission of fruits, and the temperature without fluctuation can significantly inhibit respiration (Pan et al., 2019). Our results showed that the combination of VPC and LTF can inhibit respiration more effectively than the combination of VPC and OZ after storage for 3–9 days.…”
Section: Resultsmentioning
confidence: 99%
“…The method of Pan et al. (2019) was used to achieve low‐temperature fluctuation (VPC+LTF) storage conditions with slight modifications. The cherry samples were placed in a homemade temperature fluctuation box.…”
Section: Methodsmentioning
confidence: 99%
“…Tano et al (2007) found that mushrooms (4-14°C) and mature green tomatoes (3-13°C) stored under TF conditions had significantly less firmness than that under constant temperature. Pan et al (2019) found peach exposed to higher TF (1 ± 2°C) had lower firmness, higher respiration compared with the fruit under constant storage temperature (1 ± 0°C). The quality of table grapes in cold chain decreased quickly when the temperature during cold chain fluctuating seriously (Ndraha et al, 2018;Wang et al, 2017).…”
mentioning
confidence: 81%